Influence of nano-TiO2, nano-Fe2O3, nanoclay and nano-CaCO3 on the properties of cement/geopolymer concrete - Abdalla, Jamal A. (2022)
In past decades, researchers have tried to improve the durability of concrete by integrating supplementary cementitious materials into concrete. Recent advancements in the field of nano-engineered concrete have reported that nanomaterials significantly improve the mechanical and durability properties of concrete. This paper provides a comprehensive summary of recent developments on the use of nanomaterials as a performance enhancer in cement/geopolymer concrete. Many significant correlations associated with the reinforcement of cementitious matrices using nano-TiO2, nano-Fe2O3, nanoclay/metakaolin, and nano-CaCO3 were studied. Performance aspects such as fresh properties, microstructure, mechanical and durability characteristics, and the influence of various particle sizes have been reviewed. The findings from this review confirm the feasibility of using the nanomaterials in cement concrete, with the required properties of building materials. It is also expected that this review provides better insight into using nanomaterials in concrete for the benefit of academic and fundamental research and promotes its practical application in the construction industry.